Airline Responsibility for Loss and Damage to Passeger Goods From the Perspective of Wahbah Az-Zuhaili - Ummi Kalsum Siregar; Tetty Marlina Tarigan (Mahesa Research Center, 2023)
Responsibility can be defined as acondition of being obliged to bear something if there is something that can be claimed, dusputed, allowed, and so on, in the context of legal of legal rwlations between one person and another with more emphasis on individual interests, privat in nature. this paper aims to find out how airlines are responsible for damage and loss of passeger goods. In order to approach this problem, a reference to qualiltative theory is used. data data was collected through secondary and primary data sources and analyzed qualitatively. This study councludes that even the students who damage the goods are caused by general workers, so the one who guarantees it is the instructor because he is the one who is basically resposible, so it is as if he himself did the damage